From Philosophy to Praxis: Relevance of Charles S. Peirce’s Pragmatism in Islamic Education - M. Aba Yazid; Ma'mun (International Tatho Academics, 2026)
The purpose of this study is to describe Charles Sanders Peirce's pragmatism and its relevance to the Islamic Education paradigm. This qualitative study is in the form of a literature review. Content analysis was used in this study. Data was obtained through documentation techniques. The results of the study show that pragmatism is a school of thought in philosophy which assumes that the truth value of a concept or theory is determined by its usefulness in practice. Meanwhile, the pragmatic approach in Islamic education can be implemented by providing students with real experiences so that they can hone their critical and creative thinking skills. This research contributes to the understanding that the philosophical thoughts of Charles S. Peirce, especially in the field of pragmatism, have great potential to enrich and expand education in Islam